2008
DOI: 10.1345/aph.1l045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Pharmacists' Interventions in French Hospitals: Results of a Multicenter Study

Abstract: In French hospitals, pharmacists contribute to preventing DRPs during medication order validation. This study suggests that a few types of drugs and errors constitute a substantial proportion of PIs. Knowledge of the most frequent DRPs could significantly increase the efficiency of clinical PIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
46
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 25 publications
15
46
2
5
Order By: Relevance
“…One way to achieve true change and overcome the barriers would be to perform studies that can demonstrate how a pharmacist could produce better clinical and economic outcomes to patient care. Numerous studies have found that pharmacists can improve patient safety and outcomes [14][15][16][17][18][19][20][21][22][23]. However, no study has been performed in Iran, because clinical pharmacy is a new profession and at the moment, only a few clinical pharmacists are practicing in this country.…”
Section: Discussionmentioning
confidence: 99%
“…One way to achieve true change and overcome the barriers would be to perform studies that can demonstrate how a pharmacist could produce better clinical and economic outcomes to patient care. Numerous studies have found that pharmacists can improve patient safety and outcomes [14][15][16][17][18][19][20][21][22][23]. However, no study has been performed in Iran, because clinical pharmacy is a new profession and at the moment, only a few clinical pharmacists are practicing in this country.…”
Section: Discussionmentioning
confidence: 99%
“…Ainsi, la quasi-totalité des interventions pharmaceutiques (92 %) a été acceptée par les cliniciens, signe d'une efficace collaboration avec l'équipe pharmaceutique. Des études réalisées en France retrouvent des taux d'acceptation proches de 80 % [16,17].…”
Section: Discussionunclassified
“…As is often the case, each medical discipline tends to prescribe the drugs, which they consider to be within their domain. Moreover, in France, oversight and approval of prescriptions for in-patients by the hospital pharmacist is still uncommon although this practice is increasing [46]. It seems appropriate to establish a policy aimed at avoiding the use of hazardous drug combinations.…”
Section: In Practicementioning
confidence: 99%